Accuracy of Mothers Reports Regarding Vaccination Status of Their Children in Urban Bangladesh - Selimuzzaman, ABM; Ullah, MA; Haque, MJ (TAJ: Journal of Teachers Association, 2009)
With the primary view to test the accuracy of the mothers reports regarding their children's immunization status, this study was carried out in the metropolitan areas of Rajshahi among the mothers of 12-23 months old children, Total 1500 mothers were included in this study as sample units by two stage cluster sampling method. In this study, child immunization card retention rate was 66.22%, Majority of the mothers reported accurately about their children's DPT (76%) and measles (85%) vaccination status. It suggests that urban mothers statements about their children' vaccination status is reliable. And in case of DPT young and educated mothers with higher family economic status and having fewer children were comparatively more reliable than others. Field workers should motivate and encourage the mothers to preserve their children's immunization cards. doi: 10.3329/taj.v21i1.3217 TAJ 2008; 21(1): 40-43